Maternal BCG primes for enhanced health benefits in the newborn. Issue 3 (March 2022) - Schaltz-Buchholzer, Frederik; Bjerregård Øland, Christian; Berendsen, Mike; Bjerregaard-Andersen, Morten; Stjernholm, Elise Brenno; Golding, Christian N; Monteiro, Ivan; Aaby, Peter; Benn, Christine Stabell
Highlights: In RCTs, neonatal BCG provided protection against non-TB infections. Neonatal BCG vaccination especially reduced the risk of fatal neonatal sepsis. Recent studies have associated maternal BCG scars with improved offspring outcomes. In a cohort of 10, 598 newborns, maternal BCG scar halved the risk of fatal sepsis. The protection inferred by maternal BCG was particularly strong for male newborns. Summary: Objectives: Bacille Calmette-Guérin (BCG) vaccination lowers the risk of severe infection; we tested whether effects are modulated by maternal BCG in a large cohort of BCG-vaccinated newborns from Guinea-Bissau. Methods: Maternal BCG scar status were inspected at enrolment in a BCG trial conducted from 2014 to 17 in Bissau, Guinea-Bissau. We tested associations with background factors for potential confounding; maternal age affected effect estimates >5% and accordingly, all analyses were adjusted for maternal age. Hospitalization data was collected prospectively and assessed in Cox-models providing adjusted Incidence Rate Ratios (aIRRs). In-hospital risk of death (case-fatality) risk was assessed using binomial regression providing adjusted Risk Ratios (aRRs). Results: 60% (6, 309/10, 598) of mothers had a scar. The maternal-scar/no-scar admission aIRR was 0.96 (0.81–1.14) from 0 to 6 weeks and 1.12 (0.97–1.28) for 6 weeks-3 years. The 6-week in-hospital case-fatality infection aRR was 0.59 (0.34–1.05); 0.40 (0.17–0.91) for males and 0.86 (0.38–1.94) for females. Protection was especially evident against sepsis, the overall 6-week aRR=0.49 (0.26–0.91); no effect was observed for non-infectious deaths or after 6 weeks of age. Effects were similar across BCG strains and multivariate models adjusted for socioeconomic status did not affect estimates. Conclusion: Among BCG-vaccinated newborns, there was a trend for fewer in-hospital deaths from infection associated with maternal BCG priming, especially for males. Providing BCG to adults without a vaccination scar might enhance their offspring's capacity to handle severe infections. Brief 40-word summary: Within a trial comparing BCG strains for their overall effects on morbidity and mortality in Guinea-Bissau, vertical priming with BCG (represented by the maternal BCG scar) was associated with beneficial sex-differential effects on offspring survival.